Towards designing anisotropy for ductility enhancement: A theory-driven investigation in Mg-alloys. (1st June 2017) - Basu, Shamik; Dogan, E.; Kondori, B.; Karaman, I.; Benzerga, A.A.
Abstract: Plastic anisotropy is often invoked to rationalize low formability in strongly anisotropic materials. Analysis based on homogenization theory suggests, however, that certain forms of plastic anisotropy may hinder ductile damage under any triaxial stress state or loading orientation. Here, a proof-of-concept is demonstrated in the case of Mg alloys. Two textures produced by severe plastic deformation of Mg-3Al-1Zn alloy, while keeping the grain sizes nearly the same, are compared with the well-known rolling texture in terms of their anisotropy–ductility correlations at room temperature. For each material, the 3D plastic anisotropy is characterized using tensile and compression specimens whereas the ductility is determined using smooth and round notched tensile bars. A simple micromechanical model is proposed to rationalize the trends. The main finding suggests that plastic anisotropy can be altered to aid ductility. Perspectives for how to harness anisotropy in material design are presented. Graphical abstract: Image 1